Genetics of the Colombian paso horse, phylogenetics, biotype, and gaits (2019)
The Colombian paso horse, also known as Colombian creole paso horse, the most important horse breed in Colombia, has been selected for conformation and gaits for at least the last 50 years. We hypothesize that this selection has led to the formation of two differentiated breeds. Hence, the aim of the study was to establish whether or not the Colombian paso horse corresponds to one or more breeds based on pedigree, genetic, and phenotypic data. To test our hypotheses, data from Colombian paso horses (220,000 pedigree records, 132,637 autosomal microsatellite genotypes, 900 X chromosome microsatellite genotypes, 198 mitochondrial d-loop sequences, conformation and kinematic measurements for 172 horses, and a DMRT3 nonsense mutation genotypes for 153 horses) were analyzed. The results indicated that there are significant genetic and phenotypic differences between the Colombian paso horses, where a continuum genetic differentiation has been occurring during the last 3 generations traced, in particular between the Colombian paso fino and the other groups. Also, there are significant kinematic and DMRT3 differences between the Colombian paso horse’s gaits, and those parameters can be used partially to select and control the horses’ gait performance. Finally, phylogenetic analyzes showed that the Colombian paso horses had a complex breed origin and that these horses share an evolutionary history with specific haplotypes, even, some of those haplotypes represent an ancestral Iberian haplogroup which had been described in just few modern horses until the present study. Hence, all the results strongly suggested that the Colombian paso horse breed became two breeds: the Colombian paso fino horse breed and the Colombian trocha and trot horse breed. In addition, the DMRT3 gene does not play a major role in controlling the trocha and the Colombian trot gaits. Therefore, additional genes or other DMRT3 mutations likely influence these gaits. This study has settled down the genetic and phenotypic foundations of these Colombian paso horse breeds; and also, has evidenced for the first time a breed formation process where the role of the microevolutionary process was registered by means of genetic data and phenotypic differentiation.